Halogen-doped lithium sulfide, method for producing the same, sulfide-based solid electrolyte, method for producing the same, and use
Patent Information
- Application Number
- CN202611287435.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-16
AI Technical Summary
1.构建多级晶格缺陷,降低锂离子迁移势垒
Smart Images

Figure CN122931014A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte preparation technology, and more specifically, to a halogen-doped lithium sulfide and its preparation method, a sulfide-based solid electrolyte and its preparation method, and its applications. Background Technology
[0002] Among the key materials for all-solid-state lithium batteries, sulfide solid electrolytes possess advantages such as high room-temperature ionic conductivity, good mechanical flexibility, excellent contact with the electrode interface, and good processing performance, making them one of the solid electrolyte systems with the best industrialization prospects. Lithium sulfide, as the core precursor material for sulfide solid electrolytes, directly determines the ion conduction efficiency, structural stability, and electrochemical compatibility of the final sulfide electrolyte through its purity, microstructure, crystal structure, and defect state.
[0003] Currently, conventional lithium sulfide preparation processes mostly employ traditional methods such as high-temperature solid-state sintering, solvothermal synthesis, and mechanical ball milling. The synthesized lithium sulfide crystals have complete structures and few intrinsic defects. However, sulfide solid electrolytes prepared from these raw materials generally suffer from the following defects: a single lattice migration channel, high resistance to lithium-ion migration, and low room-temperature ionic conductivity, which limits the rate performance of the battery; insufficient crystal structure stability, which makes the structure prone to collapse during charge and discharge, leading to excessively rapid degradation of battery cycle life; and poor interfacial compatibility between the electrolyte and the positive and negative electrode materials, which easily generates interfacial impedance and exacerbates polarization.
[0004] To improve the electrochemical performance of sulfide electrolytes, single-component doping with metallic or non-metallic elements is often employed. While this can introduce lattice defects and enhance ion conductivity to some extent, it suffers from problems such as poor doping uniformity, limited modification effect, complex preparation process, high production cost, and decreased chemical stability of the doped material. Halogen elements, due to their moderate atomic radius and controllable electronegativity, possess unique advantages in lattice regulation and defect construction (patents CN120565789A and CN120280542A). However, at present, controllable synthesis processes for iodine-directed doping modification of lithium sulfide are still lacking, and there is a lack of mature, simple, and low-cost preparation schemes. Furthermore, the lattice regulation mechanism of lithium sulfide by iodine doping and its synergistic optimization effect on the overall performance of subsequent sulfide solid electrolytes have not been fully explored and applied. Summary of the Invention
[0005] The purpose of this invention is to overcome the above-mentioned shortcomings of the prior art and provide a halogen-doped lithium sulfide and its preparation method, a sulfide-based solid electrolyte and its preparation method, and its application.
[0006] The technical problem solved by this invention is achieved by the following technical solution.
[0007] This invention provides a halogen-doped lithium sulfide comprising the following composition: Li2x+y S x M y Where M is selected from any one of F, Br, and I, and 0.90≤x≤0.99, 0.01≤y≤0.10.
[0008] The present invention also provides a method for preparing the above-mentioned halogen-doped lithium sulfide, comprising: using sulfur powder, metallic lithium and halogen source as reaction raw materials, heating the reaction raw materials to obtain crude halogen-doped lithium sulfide, and then sintering at high temperature to obtain halogen-doped lithium sulfide.
[0009] The present invention also provides a method for preparing a sulfide-based solid electrolyte using the above-mentioned halogen-doped lithium sulfide, comprising: ball milling the above-mentioned mixture of halogen-doped lithium sulfide, P2S5 and LiCl to obtain a uniform powder, and then sintering it at high temperature to obtain a sulfide-based solid electrolyte.
[0010] The present invention also provides a sulfide-based solid electrolyte prepared by the above-described preparation method, wherein the composition of the sulfide-based solid electrolyte is Li a P2S b M c Cl3, wherein M is selected from any one of F, Br, and I, 17.48 < a < 19.64, 12.20 < b < 12.92, 0.08 < c < 0.80.
[0011] The present invention also provides the application of the above-mentioned halogen-doped lithium sulfide and / or the above-mentioned sulfide-based solid electrolyte in a battery.
[0012] The present invention has the following beneficial effects: 1. Constructing multi-level lattice defects to reduce the lithium-ion migration barrier. Halogen atoms are incorporated into the lithium sulfide matrix through two mechanisms: substitution of sulfur lattice sites and formation of interstitial structures. This pre-introduces controllable concentrations of lithium vacancies and lattice defects. Furthermore, combined with chloride ion co-doping, the lithium-phosphorus-sulfur master lattice is synergistically regulated, further optimizing the lithium-ion diffusion channels. Compared to pure-phase and single-halogen doped systems, the lithium-ion migration activation energy is significantly reduced, achieving high ion conductivity at room temperature.
[0013] 2. Stabilizes the crystal framework and inhibits phase transformation and structural degradation. A mixture of halogen-doped lithium sulfide, P2S5, and LiCl was ball-milled to obtain a uniform powder, which was then sintered at high temperature to prepare a sulfide-based solid electrolyte. Halogen co-doping enhances the chemical bond energy within the crystal lattice and improves the rigidity of the crystal structure. Under charge-discharge cycles and temperature fluctuations, it effectively suppresses lattice distortion, phase transformation, and grain pulverization, maintains the stability of the main phase structure of silver-sulfur germanium ore, and ensures the long-term consistency of the electrolyte's physicochemical properties.
[0014] 3. Achieve uniform solid solution of halogen elements and reduce the formation of impurity phases. Halogen-doped lithium sulfide precursors are prepared by solid-state reaction to ensure accurate halogen stoichiometry and uniform dispersion. After mechanical alloying and solid-state sintering, the precursors are combined with phosphorus pentasulfide and lithium chloride to uniformly dissolve chlorine-iodine, chlorine-fluorine or bromine-fluorine halogens in the crystal lattice, which greatly reduces the content of impurity phases such as lithium halides and free sulfides.
[0015] 4. Simplify the reaction system and improve process stability and controllability. The entire process adopts a solid-phase synthesis route, eliminating problems such as solvent residue and material hydrolysis caused by liquid-phase synthesis; the reaction temperature range is mild, the parameter window is wide, the raw material conversion is sufficient, the product performance deviation between batches is small, and the process is highly repeatable. Attached Figure Description
[0016] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0017] Figure 1 This is the synthesis roadmap. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0019] The purpose of this invention is to provide a method for preparing halogen-doped lithium sulfide and a sulfide solid electrolyte, which overcomes the defects of traditional lithium sulfide raw materials with simple structure and weak ion conductivity. By precisely doping with halogens to control the lattice structure of lithium sulfide, a rich lithium ion transport channel is constructed. At the same time, the preparation process of the sulfide solid electrolyte is simplified, the synthesis conditions are reduced, and the ionic conductivity, structural stability and electrochemical compatibility of the sulfide solid electrolyte are further improved.
[0020] The following provides a detailed description of a halogen-doped lithium sulfide and its preparation method, a sulfide-based solid electrolyte and its preparation method, and its applications, provided by embodiments of the present invention.
[0021] In a first aspect, the present invention provides a halogen-doped lithium sulfide comprising the following composition: Li 2x+y S x M yWhere M is selected from any one of F, Br, and I, 0.90≤x≤0.99, 0.01≤y≤0.10. The halogen-doped lithium sulfide provided above, through halogen-directed doping modification of lithium sulfide, introduces a large number of lithium-ion transport channels by halogen atoms replacing sulfur lattice sites and forming interstitial defects in the lattice, thereby reducing the lithium-ion migration energy barrier.
[0022] Secondly, the present invention also provides a method for preparing the above-mentioned halogen-doped lithium sulfide, comprising: using sulfur powder, lithium metal and halogen source as reaction raw materials, heating the reaction raw materials to obtain crude halogen-doped lithium sulfide, and then sintering at high temperature to obtain halogen-doped lithium sulfide.
[0023] In some alternative embodiments, the method for preparing halogen-doped lithium sulfide includes the following steps: Step a: A certain proportion of sulfur powder, industrial-grade lithium metal, and halogen source are directly placed into the titanium material reaction device to obtain the reaction materials; Step b: Place the reactants obtained in step a into a titanium reaction apparatus, and use a protective gas and stirring method to mix the reactants evenly and react as fully as possible. The stirring speed is 20-40 rpm, the stirring time is 4-8 h, and the reaction temperature is 200-300℃ to obtain crude halogen-doped lithium sulfide. Step c: Grind the crude lithium sulfide obtained in step b and then sieve it. Step d: The crude lithium sulfide obtained in step c is calcined at 300-400℃ for 2-4 hours; after natural cooling, it is pulverized to obtain high-purity Li with uniform particle size and uniform doping. 2x+y S x I y Powder.
[0024] Thirdly, this invention also provides a method for preparing a sulfide-based solid electrolyte using the aforementioned halogen-doped lithium sulfide, comprising: ball milling a mixture of halogen-doped lithium sulfide, P2S5, and LiCl to obtain a uniform powder, and then sintering it at high temperature to obtain a sulfide-based solid electrolyte. In this invention, halogen atoms are incorporated into the lithium sulfide matrix through two methods: substituting sulfur lattice sites and forming interstitial lattice structures, to obtain halogen-doped lithium sulfide; further optimization of the lithium-ion diffusion channel is achieved by combining chloride ion co-doping with the synergistic regulation of the lithium-phosphorus-sulfur main lattice. Compared to pure-phase and single-halogen-doped systems, the lithium-ion migration activation energy is significantly reduced, achieving high ion conductivity at room temperature.
[0025] It is worth noting that in the process of preparing sulfide-based electrolytes using halogen-doped lithium sulfide as described above, the addition of LiCl to the reaction raw materials mainly provides Cl₂. -By entering the thiophosphate lattice, lithium vacancies are generated through anion substitution, increasing lattice disorder and lowering the lithium-ion migration barrier, significantly improving room-temperature ionic conductivity. Simultaneously, the electrolyte-lithium metal interface is optimized, constructing a stable LiCl-rich interface layer to suppress side reactions and dendrite formation. The process stabilizes the highly conductive crystalline phase and lowers the heat treatment temperature. Furthermore, the LiCl size matches S². - It has a wide solid solution range, a wide electrochemical window, and stable and inexpensive raw materials, making it the mainstream choice in academia and industrialization. Adding LiBr improves the anode interface, but reduces processing and high-voltage stability. Adding trace amounts of LiI can optimize the interface SEI, but the improvement is not significant, and increasing the amount of LiI leads to a sharp deterioration in electrolyte performance. Therefore, this invention preferably uses LiCl to prepare a sulfide-based electrolyte.
[0026] In some optional embodiments, the method for preparing a sulfide-based solid electrolyte includes the following steps: Step a: Operate in an inert glove box. Weigh each raw material powder according to the molar ratio of halogen-doped lithium sulfide:P2S5:LiCl of 8:1:3. P2S5 and LiCl are both battery-grade high-purity raw materials, pre-vacuum dried to remove surface adsorbed moisture and trace impurities, avoiding oxidation and hydrolysis byproducts during the reaction and ensuring a pure phase electrolyte structure. Place the weighed raw materials together into a tungsten carbide ball mill jar, matching zirconium oxide grinding balls at a ball-to-material mass ratio of 20:1-30:1. After sealing and evacuating, purge with high-purity argon for protection. Set the ball mill speed to 300-500 r / min and mill in stages for 4-6 hours. This step achieves microscopic uniform composite of raw materials through mechanical force, while refining the powder particle size and constructing abundant interfacial defects, providing active sites for subsequent solid-phase reactions and avoiding raw material agglomeration and uneven local reactions.
[0027] Step b: Transfer the ball-milled, homogeneous powder obtained in step a into a sealed quartz reaction tube, maintaining an inert argon atmosphere throughout the process; heat to 350-450℃ at a uniform rate of 3-5℃ / min, and sinter at this temperature for 4-8 hours. This step promotes a thorough solid-phase reconstruction reaction between the precursor, phosphorus pentasulfide, and lithium chloride, allowing chlorine, chlorofluorine, or bromofluorine to be uniformly doped into the lithium phosphorus sulfide lattice, forming a stable single-phase solid solution structure of silver-sulfur germanium ore; strictly control the sintering temperature and holding time to avoid high-temperature impurity phase precipitation, lattice collapse, and element volatilization and loss.
[0028] Step c: After the sintering obtained in step b is completed, let it cool naturally to room temperature in the furnace. Take out the sintered product in an inert glove box, crush it in a pulverizer, and finally obtain a sulfide-based solid electrolyte with uniform powder, stable structure and high ionic conductivity.
[0029] Fourthly, the present invention also provides a sulfide-based solid electrolyte prepared by the above-described preparation method, wherein the composition of the sulfide-based solid electrolyte is Li a P2S b M c Cl3, wherein M is selected from any one of F, Br, and I, 17.48 < a < 19.64, 12.20 < b < 12.92, 0.08 < c < 0.80.
[0030] In some alternative embodiments, the sulfide-based solid electrolyte has an ionic conductivity of 1.0-7.8 mS / cm.
[0031] As can be seen from the above, this invention develops a simple, mild, and uniformly doped halogen-doped lithium sulfide controllable preparation method. By precisely controlling the crystal structure and lattice defects of lithium sulfide through halogen doping, a sulfide solid electrolyte with high ionic conductivity, high structural stability, and low interfacial impedance is prepared. This solves the industry pain points of poor cycle stability and complex modification processes of sulfide electrolytes in the prior art, and has important practical significance for promoting the large-scale application of high-performance all-solid-state lithium batteries.
[0032] Fifthly, the present invention also provides the application of the above-mentioned halogen-doped lithium sulfide and / or the above-mentioned sulfide-based solid electrolyte in a battery.
[0033] The present invention will be further described below with reference to embodiments.
[0034] The preparation methods of halogen-doped lithium sulfide in Examples 1-5 include the following steps: Step a, mixing: All material taking, reaction, screening and crushing operations are completed in an argon glove box with water and oxygen content <0.1ppm; the reaction vessel is a titanium reactor with stirring, and is protected by argon gas throughout the process; Step b, heating reaction: the stirring speed is 20 rpm, the stirring time is 6 hours, the reaction temperature is 240℃, and then it is allowed to cool to room temperature.
[0035] Step c: The crude lithium sulfide obtained is ground and then passed through a 300-mesh sieve to obtain crude halogen-doped lithium sulfide. Step d, calcination reaction: The calcination temperature was 350℃, and the calcination time was 3 hours. The grinding speed was 25000 rpm, and the grinding time was 30 seconds. Finally, high-purity Li with uniform particle size and uniform doping was obtained. 2x+y S x I y Powder. System uniform constraints: The total molar amount of Li, S, and I atoms satisfies the lithium-sulfur host matrix framework, and the molar number of S atoms x=1. y, chemical formula unified as Li 2(1-y)+y S 1-y Iy ; y represents the molar percentage of iodine atoms, which are 0, 0.02, 0.04, 0.05, 0.06, and 0.08, respectively.
[0036] The preparation method for the corresponding solid electrolyte includes the following steps: Step a: All pre-processing operations were conducted in an argon glove box with a water and oxygen content of <0.1ppm. The raw material was the halogen-doped lithium sulfide precursor Li prepared in Examples 1-6 above. 2x+y S x I y Battery-grade P2S5, anhydrous LiCl; the precursor molar ratio is fixed at 8:1:3; Step b: A sealed tungsten carbide ball mill jar under argon protection, with a ball-to-material mass ratio of 25:1, a ball milling speed of 350 r / min, and segmented ball milling for 4 hours; the sintering process uses a quartz tube under argon protection, with a sintering heating rate of 5℃ / min, a sintering temperature of 400℃, and a sintering time of 6 hours.
[0037] Step c: After sintering, cool with the furnace; after cooling, pulverize in a pulverizer to obtain the target silver-germanium sulfide-type solid electrolyte.
[0038] Example 1: y=0.02 (1) When the reactants are fed in an atomic molar ratio of Li:S:I = 1.98:0.98:0.02, the product obtained is Li 1.98 S 0.98 I 0.02 .
[0039] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.84 P2S 12.84 I 0.16 Cl3.
[0040] Example 2: y=0.04 (1) When the reactants are fed in an atomic molar ratio of Li:S:I = 1.96:0.96:0.04, the product obtained is Li 1.96 S 0.96 I 0.04 .
[0041] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.68 P2S 12.68 I 0.32 Cl3.
[0042] Example 3: y=0.05 (1) When the reactants are fed in an atomic molar ratio of Li:S:I = 1.95:0.95:0.05, the product obtained is Li 1.95 S 0.95 I0.05 .
[0043] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.60 P2S 12.60 I 0.40 Cl3.
[0044] Example 4: y=0.06 (1) When the reactants are fed in an atomic molar ratio of Li:S:I = 1.94:0.94:0.06, the product obtained is Li 1.94 S 0.94 I 0.06 .
[0045] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.52 P2S 12.52 I 0.48 Cl3.
[0046] Example 5: y=0.08 (1) When the reactants are fed in an atomic molar ratio of Li:S:I = 1.92:0.92:0.08, the product obtained is Li 1.92 S 0.92 I 0.08 .
[0047] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.36 P2S 12.36 I 0.48 Cl3.
[0048] Example 6: The steps are basically similar to those in Example 3, except that: (1) When the reactants are fed in an atomic molar ratio of Li:S:LiF = 1.95:0.95:0.05, the product obtained is Li. 1.95 S 0.95 F 0.05 .
[0049] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.60 P2S 12.60 F 0.40 Cl3.
[0050] Example 7: The steps are basically similar to those in Example 3, except that: (1) When the reactants are fed in an atomic molar ratio of Li:S:LiBr = 1.95:0.95:0.05, the product obtained is Li 1.95 S 0.95 F 0.05 .
[0051] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.60 P2S 12.60 Br 0.40 Cl3.
[0052] Comparative Example 1: y=0 (1) When the atomic molar ratio of Li:S:I = 2:1:0 is used, the product obtained is Li2S, which is a pure phase and has no iodine lattice defects.
[0053] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 19 P2S 13 Cl3.
[0054] Comparative Example 2 The steps are basically similar to those in Example 1, except that y=0.1 during the preparation process, and the product obtained is Li. 1.90 S 0.90 I 0.1 .
[0055] (2) Using the same ball milling and sintering process, the corresponding solid electrolyte is Li 18.20 P2S 12.20 I 0.80 Cl3.
[0056] Comparative Example 3 The steps are basically similar to those in Example 3, except that the reaction temperature in step b of the halogen-doped lithium sulfide preparation process is 400°C.
[0057] Comparative Example 4 The steps are basically similar to those in Example 3, except that the reaction temperature in step b of the halogen-doped lithium sulfide preparation process is 150°C.
[0058] Comparative Example 5 Referring to the example provided in application number CN202511204978.4, lithium sulfide powder was prepared by using elemental iodine as a sulfur-end blocking additive and synthesizing lithium sulfide by a solid-phase method (wherein, elemental iodine only acts on sublimed sulfur to form an I2-S8 blend, which is removed in gaseous form during the heating process, and the product is pure lithium sulfide). Using this lithium sulfide as raw material, a solid electrolyte was synthesized according to Example 1.
[0059] Performance testing The all-solid-state battery was assembled in a high-purity argon glove box (H2O and O2 contents both below 0.1 ppm). It used LiNbO3-coated NCM811 as the positive electrode active material, which was then mixed uniformly with a sulfide solid electrolyte prepared from halogen-doped lithium sulfide and conductive carbon at a mass ratio of 8:1:3 using a dry pressing process. A dense electrolyte separator layer was first formed by pre-pressing the solid electrolyte powder, followed by the deposition of the positive electrode composite material. A lithium metal negative electrode was then assembled on the other side. The mixture was cold-pressed at 350 MPa for 3 minutes to obtain an integrated solid-state cell, which was then encapsulated in a CR2032 button cell casing. Electrochemical testing was conducted at 25°C, with a voltage range of 2.6–4.2 V. After two cycles of activation at 0.05C, long-cycle charge-discharge testing was performed at 0.1C, and the capacity retention rate was calculated by normalizing the second discharge capacity. Electrochemical impedance spectroscopy was used to characterize the battery interface impedance, with a test frequency range of 1 MHz to 0.1 Hz. The room temperature ionic conductivity of the solid electrolyte was calculated using a stainless steel blocking electrode combined with AC impedance testing.
[0060] Test Results The test results of Examples 1-7 and Comparative Examples 1-5 are shown in Table 1 below: Table 1
[0061] As can be seen from Table 1, the ionic conductivity and cycle performance of the sulfur-based solid electrolyte prepared by lithium sulfide without iodine doping are lower than those of halogen-doped lithium sulfide. When iodine doping y=0.05, its ionic conductivity and capacity retention are the highest. This is mainly due to the precise control of lithium sulfide crystal structure and lattice defects by iodine doping.
[0062] In summary, this invention provides a halogen-doped lithium sulfide and its preparation method, a sulfide-based solid electrolyte and its preparation method, and its applications. First, lithium sulfide is modified by halogen-directed doping, allowing halogen atoms to replace sulfur lattice sites and form interstitial defects, introducing a large number of lithium-ion transport channels and lowering the lithium-ion migration barrier. Then, chlorine co-doping is combined to synergistically regulate the lithium-phosphorus-sulfur lattice structure, further optimizing the lattice defect distribution. The solution provided by this invention has the following advantages and characteristics: 1) This invention first modifies lithium sulfide through halogen-directed doping, introducing numerous lithium-ion transport channels by halogen atoms replacing sulfur lattice sites and forming interstitial defects, thereby lowering the lithium-ion migration energy barrier. Then, it combines this with chlorine co-doping to synergistically regulate the lithium-phosphorus-sulfur lattice structure, further optimizing the lattice defect distribution. The resulting solid-state electrolyte exhibits significantly higher room-temperature ionic conductivity than traditional undoped and single-halogen-doped lithium-phosphorus-sulfur-chlorine systems, effectively improving the battery's rate charge / discharge performance.
[0063] 2) Co-doping with chlorine-iodine, chlorine-fluorine, or bromo-fluorine dihalogens can enhance the lattice bonding strength of the lithium phosphorus-sulfur matrix, suppress lattice distortion, structural collapse, and phase transformation during charge and discharge, and prevent electrolyte pulverization failure under long-term cycling. Simultaneously, it reduces side reactions at the electrolyte-electrode interface, slows the increase in interfacial impedance, significantly extends the cycle life of all-solid-state lithium batteries, and improves the long-term reliability of the device.
[0064] 3) An iodine-doped lithium sulfide precursor is prepared by a one-step solid-state reaction of lithium metal, sulfur powder, and elemental iodine. The reaction is carried out in a closed inert atmosphere, which can effectively suppress the sublimation and loss of elemental iodine, ensure accurate iodine element measurement, uniform solid solution in the lithium sulfide lattice, and prevent the precipitation of lithium iodide impurity phases. The precursor is then composited and sintered with phosphorus pentasulfide and lithium chloride in a specific ratio. The two halogens, iodine and chlorine, can be uniformly distributed in the overall lattice. The product is mainly composed of a single silver-sulfur germanium mineral phase with high phase purity.
[0065] 4) The process is simple and controllable, suitable for large-scale production. The entire preparation process mainly consists of solid-phase ball milling and low-temperature sintering. The reaction conditions are mild, requiring no high temperature and high pressure, complex solvent systems, or special catalysts. The operation steps are simple. Raw materials are readily available, and the entire process can be completed in conventional inert atmosphere equipment. The process has good repeatability, low production cost, and is convenient for industrial-scale batch preparation.
[0066] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A halogen-doped lithium sulfide, characterized in that, Substances comprising the following components: Li 2x+y S x M y Where M is selected from any one of F, Br, and I, and 0.90≤x≤0.99, 0.01≤y≤0.
10.
2. A method for preparing halogen-doped lithium sulfide according to claim 1, characterized in that, include: Using sulfur powder, metallic lithium, and halogen source as reaction raw materials, the reaction raw materials are heated to obtain crude halogen-doped lithium sulfide, which is then sintered at high temperature to obtain halogen-doped lithium sulfide.
3. The preparation method according to claim 2, characterized in that, The preparation of the crude halogen-doped lithium sulfide includes: placing the reaction raw materials in a titanium reaction apparatus, introducing a protective gas, controlling the stirring speed to be 20-40 rpm, stirring for 4-8 hours to ensure uniform mixing of the reaction raw materials, and then heating the reaction at 200-300℃ to obtain the crude halogen-doped lithium sulfide.
4. The preparation method according to claim 3, characterized in that, The preparation of the halogen-doped lithium sulfide includes: grinding the crude lithium sulfide obtained by heating reaction and then sieving it; calcining it at 300-400℃ for 2-4 hours; and pulverizing it after natural cooling, controlling the pulverizing speed at 25000 rpm and the pulverizing time at 30 seconds to obtain high-purity halogen-doped lithium sulfide powder with uniform particle size and uniform doping.
5. A method for preparing a sulfide-based solid electrolyte using halogen-doped lithium sulfide, characterized in that, include: A mixture of halogen-doped lithium sulfide, P2S5, and LiCl is ball-milled to obtain a uniform powder, which is then sintered at high temperature to prepare a sulfide-based solid electrolyte. The halogen-doped lithium sulfide is the halogen-doped lithium sulfide described in claim 1 or the halogen-doped lithium sulfide prepared by any one of claims 2-4.
6. The preparation method according to claim 5, characterized in that, The preparation of the uniform powder includes: operating in an inert glove box, placing halogen-doped lithium sulfide:P2S5:LiCl together in a tungsten carbide ball mill jar according to a molar ratio of 8:1:3, matching zirconium oxide grinding balls according to a ball-to-material mass ratio of 20:1-30:1, sealing and evacuating the jar, and then filling it with high-purity argon gas for protection; setting the ball mill speed to 300-500 r / min, and ball milling in stages for 4-6 hours to obtain uniform powder.
7. The preparation method according to claim 6, characterized in that, The preparation of the sulfide-based solid electrolyte includes: transferring the ball-milled and composite uniform powder into a sealed quartz reaction tube, maintaining an inert argon atmosphere throughout the process; heating to 350-450℃ at a uniform rate of 3-5℃ / min, sintering at a constant temperature for 4-8 hours, and then naturally cooling to room temperature with the furnace after sintering. The sintered product is then removed from an inert glove box and pulverized by a pulverizer to finally obtain a sulfide-based solid electrolyte with uniform powder, stable structure, and high ionic conductivity.
8. A sulfide-based solid electrolyte prepared by the method according to any one of claims 5-7, characterized in that, The composition of the sulfide-based solid electrolyte is Li a P2S b M c Cl3, wherein M is selected from any one of F, Br, and I, 17.48 < a < 19.64, 12.20 < b < 12.92, 0.08 < c < 0.
80.
9. The sulfide-based solid electrolyte according to claim 8, characterized in that, The ionic conductivity of the sulfide-based solid electrolyte is 1.0-7.8 mS / cm.
10. The application of the halogen-doped lithium sulfide according to claim 1 and / or the sulfide-based solid electrolyte according to any one of claims 8-9 in a battery.
Citation Information
Patent Citations
Modified sulfide solid electrolyte and preparation method and application thereof
CN120280542A
Iodine compound coated sulfide solid electrolyte and preparation method and application thereof
CN120565789A
Method for preparing lithium sulfide and sulfide solid electrolyte thereof based on doping combustion method
CN120793851A